Volume and Intensity of Locomotor Activity in International Men's Field Hockey Matches Over a 2-Year Period - Carl A. James; Oliver R. Gibson; Aishwar Dhawan; Craig M. Stewart; Ashley G. B. Willmott (Frontiers Media S.A., 2021)
The locomotor demands of international men's field hockey matches were investigated across positions (DEF, MID, FWD) and playing quarters. Volume (i.e., total values) and intensity (i.e., relative to playing time) data were collected using 10-Hz GPS/100-Hz accelerometer units from the #11 world-ranked (WR) team, during 71 matches, against 24 opponents [WR 12 ± 11 (range, 1-60)]. Mean ± SD team total distance (TD) was 4,861 ± 871 m, with 25% (1,193 ± 329 m) "high-speed running" (>14.5 km h−1) and 8% (402 ± 144 m) "sprinting" (>19.0 km h−1). Reduced TD (range, −3 to 4%) and average speed (range, −3.4 to 4.7%) occurred through subsequent quarters, vs. Q1 (p < 0.05). A "large" negative relationship (r = −0.64) was found between playing duration and average speed. Positional differences (p < 0.05) were identified for all volume metrics including; playing duration (DEF, 45:50 ± 8:00 min; MID, 37:37 ± 7:12 min; FWD, 33:32 ± 6:22 min), TD (DEF, 5,223 ± 851 m; MID, 4,945 ± 827 m; FWD, 4,453 ± 741 m), sprinting distance (DEF, 315 ± 121 m; MID, 437 ± 144 m; FWD, 445 ± 129 m), and acceleration efforts (>2 m s−2; DEF, 48 ± 12; MID, 51 ± 11; FWD, 50 ± 14). Intensity variables similarly revealed positional differences (p < 0.05) but with a different pattern between positions; average speed (DEF, 115 ± 10 m min−1; MID, 132 ± 10 m min−1; FWD, 134 ± 15 m min−1), sprinting (DEF, 7 ± 3 m min−1; MID, 12 ± 4 m min−1; FWD, 14 ± 4 m min−1), and accelerations (DEF, 1.1 ± 0.3 n min−1; MID, 1.4 ± 0.2 n min−1; FWD, 1.5 ± 0.3 n min−1). Physical outputs reduced across playing quarters, despite unlimited substitutions, demonstrating the importance of optimizing physical preparation prior to international competition. Volume and intensity data highlight specific positional requirements, with forwards displaying shorter playing durations but greater high-intensity activities than defenders.